Determinants of Transfer Pricing Practices: Empirical Evidence from Manufacturing Companies Listed on the Indonesia Stock Exchange - Wastiningtyas, Sekar Arum; Sinaga, Melan (Sean Institute, 2025)
This research aims to test and analyze the influence of effective tax rate, company size, foreign ownership, tax haven and intangible assets on transfer pricing. The population used in this research is manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique in this research used a purposive sampling method, there were 15 companies that met the specified criteria and produced 75 data. The analysis technique used in this research is multiple linear regression analysis using the Statistical Package for the Social Science (SPSS) version 22.0 program. The research results show that the effective tax rate variable has no effect on transfer pricing. The variables company size and foreign ownership have a significant positive effect on transfer pricing, while the variables tax haven and intangible assets have a significant negative effect on transfer pricing.